Synthesis of Structurally Diverse N‐Substituted Quaternary‐Carbon‐Containing Small Molecules from α, α‐Disubstituted Propargyl Amino Esters. Issue 51 (13th August 2018) - Mateu, Natalia; Kidd, Sarah L.; Kalash, Leen; Sore, Hannah F.; Madin, Andrew; Bender, Andreas; Spring, David R.
Abstract: N‐containing quaternary stereocenters represent important motifs in medicinal chemistry. However, due to their inherently sterically hindered nature, they remain underrepresented in small molecule screening collections. As such, the development of synthetic routes to generate small molecules that incorporate this particular feature are highly desirable. Herein, we describe the diversity‐oriented synthesis (DOS) of a diverse collection of structurally distinct small molecules featuring this three‐dimensional (3D) motif. The subsequent derivatisation and the stereoselective synthesis exemplified the versatility of this strategy for drug discovery and library enrichment. Chemoinformatic analysis revealed the enhanced sp 3 character of the target library and demonstrated that it represents an attractive collection of biologically diverse small molecules with high scaffold diversity. Abstract : A reagent‐based diversity‐oriented synthesis approach to generate a small molecule library, starting from α, α‐disubstituted propargyl amino esters, is reported. The strategy exploited the different reactivity of the alkyne, the amine and the ester moieties. The target library represents an attractive screening collection of small molecules with high scaffold diversity covering broad areas of both molecular shape space and bioactive space.